Flowability and physical properties of wheat-unripe plantain (Musa paradisiaca) composite flour - Etti, C. J.; Yusof, Y. A.; Chang, L. S.; Ekanem, V. G. (Rynnye Lyan Resources, 2019)
This study investigated the flowability and physical properties of composite flour made from wheat flour mixed with unripe plantain flour at different ratios (70:30, 80:20 and 90:10, respectively and 100% wheat flour as control). Unripe plantain flour was chosen because it has high iron content which can resolve diet issues encountered by anaemic and celiac patients due to low iron and high protein (gluten) content in consumption of wheat bread. Physical properties of the composite flour were determined: bulk density, tapped density, angle of repose, and flowability. The proximate analysis such as ash, lipid, fibre, carbohydrate, protein, moisture content of the mixed flour was determined as well as iron content. The density of the composite flour was increased as the unripe plantain flour in the mix ratio increased, suggesting that unripe plantain flour was denser than the substituted wheat flour. The flow indexes of the composite flours show excellent freeflowing behaviour as the Carr Index (CI) and Hausner Ratio (HR) were within the range of the powder that exhibited free-flowing properties. The use of plantain flour increased the proximate composition of the composite flour except for protein content which is advantageous to the celiac patients who do not need much of the bread protein (gluten). The iron content was increased with the increase of unripe plantain flour in the mix ratio, favouring anaemic patients who require more iron. Incorporation of higher amount of unripe plantain flour reduced the swelling power of the dough which affected the bread making process.